New Insights into the Life-history Traits of the Night Shrimp Processa hemphilli (Caridea: Processidae) in the Western Atlantic - Talamonte, Natália Bosco [UNESP]; Pescinelli, Régis Augusto [UNESP]; Carvalho-Batista, Abner; Costa, Rogerio Caetano [UNESP] (My University, 2022)
We analyzed sexual dimorphism, sex ratio, relative growth, morphological sexual maturity, fecundity, embryo volume, and reproductive output of a population of the night shrimp Processa hemphilli from the Southeast coast of Brazil. Sampling was seasonally conducted, from June 2016 to April 2019 in Ubatuba, São Paulo. Our results showed the presence of sexual dimorphism in the body size, with females being larger than males. In addition, there was no difference in the overall sex ratio. However, it was possible to observe a skewed sex ratio to males in the smaller size classes, whereas females were more abundant in the larger size classes. The estimated carapace length at the onset of morphological sexual maturity of females and males was 3.6 mm and 3.2 mm, respectively. The mean fecundity of females was 285 ± 142 embryos (mean ± SD) embryos and was positively correlated with the carapace length. The embryo volume differed between the developmental stages with a constant increase in volume throughout the development between stages I and III. The mean reproductive output of females was 52.4%. Our results suggest that P. hemphilli have a pure search mating system, show sex allocation in the growth of body structures, and that females have high reproductive investment. All of these results represent the first insights into the life-history traits of the species in the western Atlantic and contribute to the knowledge about processid species.
Keywords: Decapoda; Mating system; Relative growth; Sex allocation; Sexual maturity